The deficits of the Iranian educational system in teaching children with conduct disorders - Sajad Sajadi; Ghoncheh Raheb; Masoumeh Maarefvand; Khadijeh Abolmaali Alhosseini; Abolfazl Ghasemi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: One of the serious issues in the field of children's social and mental health globally, is conduct disorder. Concerning the special problems of these children, their need for appropriate education seems vital. Thus, this study aimed to identify the educational deficiencies in the Iranian education system in terms of educating children with conduct disorder. SUBJECTS AND METHODS: This was a qualitative content analysis study of the directed type. The population was in Tehran City, Iran. This research was performed on 23 individuals using a triangulation sampling technique and in-depth interviewing. The study subjects were children with conduct disorder, their parents, teachers, and social workers, and psychology experts. The study participants were selected using a purposive sampling method, and the tool used for data collection was a checklist of questions that has been approved by 4 experts. MAXQDA (version 12) software was used for data analysis in this study. RESULTS: The obtained data suggested that the deficits of the educational system in Iran are classified into four categories, including the lack of knowledge and skills of school staff, the lack of necessary workforce, the lack of appropriate hardware facilities, and the lack of coordination and cooperation between individuals and systems. CONCLUSION: Considering the present study results, to improve the educational status of children with conduct disorder and reduce their problems, it is necessary to resolve the identified educational deficiencies as soon as possible by the government, policymakers, and educators.